Maritime Trade and Pakistan’s Merchant Marines - Haider, Syed Husnain; Naz, Dr Uzma (The journal of contemporary issues in business and government, 2021)
Being a maritime country, Pakistan is facing challenges and difficulties to take advantage of the resources of the ocean effectively. In the past, there is no strong footing and attentions have given to the maritime industry. Whereas the ocean trade has might become the backbone of Pakistan's economy. The Private and government shipping companies and the Maritime industry can boost the economic process of Pakistan. It is a need of time to pay attention to effective maritime policies and built the infrastructure for direct foreign investment. 80 % of Pakistan's trade volume is done through the ocean and a major part of this trade is through international shipping companies. New shipping business policies must be business-friendly. Provide opportunities to the Private and Public sectors both to explore the offshore resources. Provide facilitation to the tourism and hotel industry on the seashore can play a significant role in the maritime industry.